Implementation of a fuzzy-based motor controller on a behavior-based all-terrain wheeled robot - Rubrico, Jose Ildefonso U. (2002)
This research implements a low-level fuzzy motor controller in an actual behavior-based wheeled mobile robot. The robot is intended to autonomously perform a pre-programmed task (e.g. travel in a straight line for about 5 meters and then hide somewhere dark) in varied terrain. The behavior-based approach is chosen for its apparent robustness in unknown and unmodeled environments and the fuzzy-based controller due to the relative ease of controller design it affords even in the absence of a complete and precise system model. Wheeled locomotion is preferred over legged locomotion because the former allows less complex control algorithms than the latter and also because it is generally easier to implement mechanically. The robot is tested on various terrain, both man-made and naturally occuring (e.g. corridor floors, parking lots, grassy land, etc.). The performance of the speed controller is evaluated based on its transient and steady-state response characteristics.